Diet Therapy of Diabetes Type II by Paneer Dodi (Withania coagulans): A Review: Diet Therapy of Diabetes Type II by Paneer Dodi (Withania coagulans) - Saeed, Muhammad Khalid; Zahra, Naseem; Khan, Amara; Anjum, Shaheena; Ijaz, Ayesha; Shahzad, Khurram; Ahmad, Ijaz (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2026)
Globally, chronic non-communicable diseases are currently the leading cause of mortality and disability. People of various ages and socioeconomic backgrounds are affected by this diverse set of illnesses, which includes diabetes, cancer, chronic respiratory disorders, and cardiovascular diseases. Paneer Dodi is a member of the Solanaceae family and is scientifically known as Withania coagulans. Patients with diabetes, particularly those with type-2 diabetes, can benefit greatly from this enchanted herb. It aids in controlling oxidant status, kidney pro-inflammatory indicators, and blood sugar levels. The plant contains free amino acids, esterases, alkaloids, and a variety of withanolides, including withanolide A, withanolide D, withanolide E, coagulins, and withacoagulins. W. Coagulans is a potential natural substitute for synthetic drugs, which often have adverse effects, given the high incidence of diabetes mellitus. It works as an efficient antidiabetic by inhibiting the enzymes α-glucosidase and α-amylase, stimulating insulin secretion, increasing glucose absorption, and regenerating pancreatic β-cells. In diabetic patients, these measures help control hyperglycemia and improve lipid profiles. According to the review, W. coagulans shows promise for research and development of novel therapeutic products, such as antidiabetic tea, for diabetes diet therapy.